Inclusiveness in family business firms: analysing the dichotomy of social responsibility. (10th December 2019) - Lopez-Fernández, Andrée Marie; Atristain-Suárez, Connie
Family business firms (FBFs) tend to be de facto considered socially responsible as if being owned managed by a family warrants social responsibility. Are FBFs socially responsible because of the family ownership-management or a family sense of responsibility? The aim of this research is to understand the traits of FBFs' CSR engagement. It is suggested that corporate family responsibility (CFR) is inherent to family business firms with an inclusive perspective. This paper contributes to previous family business and social responsibility literature by providing concepts and a model that may further the discussion on family business social responsibility, competitive advantage and sustainable growth.